Hubungan Beban Kerja Dan Lingkungan Kerja Terhadap Stres Kerja Pada Polisi Satlantas Polres Bantul - Setyowati, Rustiana; Ulfa, Siti Maria (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2020)
In Indonesia cases of stress due to workload in the work environment of the police have occurred in several areas and have had quite serious impacts.  The Research was conducted at the traffic police Special Region of Yogyakarta in 2019. This Research is a quantitative non experimental research with correlational descriptive. Data analysis techniques using multiple linier regression analysis. Respondents as many as 50 police Bantul Police Traffic Unit, the sample uses a saturated sample.The Study aims to determine the relationship of workload and work environment to work stress of Bantul Police Traffic Unit. The results of the study stated that the traffic police unit that has a light workload of 3 people (6%) moderate 39 people (78%) and weighs 8 people(16%) while the traffic unit police who have a light work environment are 6 people (12%) moderate work environment as many as 31 people (62%) and high work environment as many as 13 people (26%). While the traffic police who have low work stress are 6 people (12%) moderate are 34 people (68%) and heavy are 10 people (20%). Data Analysis using multiple linier regression with a coefficient of deternination. 1,907 and F calculated 49,41 and F table 3,23. The results of the study concluded that there was a relationship between workload and worke nvironment on the work stress of the traffic police at Bantul Region Police Station in Yogyakarta Keywords : Load, environment, Stress, Traffic Police unit